Alcohol Use and Sexual and Physical Assault Victimization Among University Students: Three Years of Follow-Up. Issue 7 (April 2021) - Caamano-Isorna, Francisco; Adkins, Amy; Moure-Rodríguez, Lucía; Conley, Abigail H.; Dick, Danielle
The aim of this study was to determine the incidence of sexual and physical assault among university students and its association with alcohol use. The research is part of a wider cohort study (Spit for Science TM ) at a large public university in the United States. The follow-up data include the first two cohorts (2011, 2012; n = 5, 170). The dependent variables were victim of sexual assault and victim of physical assault. The independent variables were alcohol dependence and abuse according to the Diagnostic and Statistical Manual of Mental Disorders (4th ed.), cannabis use, residence, ethnicity, sexual orientation, and previous experience of sexual assault and/or physical assault. We used multilevel logistic regression for repeated measures. All data were analyzed using generalized linear mixed models. Incidence rates of sexual and physical assault (per 100 students a year) were 15.1 and 27.6 among nonabusers/dependents versus 36.4 and 56.7 among alcohol-dependent females at the first year, and 2.8 and 4.7 versus 7.7 and 23.1 at the third year; while in males, incident rates were 6.0 and 3.1 versus 18.5 and 66.6, and 2.3 and 7.4 versus 18.9 and 15.1, respectively. Our results show that alcohol abuse and dependence constitute risk factors to be victim of sexual assault in males (odds ratio [OR] = 2.21 and OR = 2.73) and alcohol dependence in females (OR = 2.16). Similarly, alcohol abuse and dependence are risk factors to physical assault among both males (OR = 1.52 and OR = 2.03) and females (OR = 1.70 and OR = 2.88). Ethnicity, sexual orientation, and whether the individual had been victimized in the past were associated with sexual assault. Regarding physical assault, cannabis use and past victimization are also risk factors. Our study has shown that assault victimization is strongly related to alcohol abuse and dependence diagnoses in both genders. Ethnicity and sexual orientation are also associated to both assaults. Our results show that incidence rates of both types of assaults were clearly higher in the first 6 months of university, probably explained by the novel and potentially risky environment.